KORELASI KEPEMIMPINAN DENGAN KOMITMEN DAN LINGKUNGAN KERJA DOSEN BERDASARKAN KRITERIA MALCOLM BALDRIGE (Suatu Survei Eksplanatori Pada Dosen Program Studi D3 Kebidanan di Propinsi Daerah Istimewa Yogyakarta) - Hesty Widyasih; Ma’mun Sutisna; Firman F Wirakusumah (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2012)
Leadership in the field of midwifery diploma 3 hopefully can bring to positive change, the increase of organization quality which is a place of midwife graduates will exist in society. Leadership factor will facilitate to build high work commitment and good work environment. Malcolm Baldrige criteria is a work management system that can measure leadership, work commitment and work environment. This study aims to analyze correlation between leadership with work commitment and environment based on Malcolm Baldrige Criteria. Research design using analytic correlative study with explanatory survey. This study is quantitative research with crosssectional study. Subject of this study is 60 lecturers of diploma 3 midwifery in Province DIY. The research was conducted in March-April 2011 using questionnaire based on Malcolm Baldrige Criteria. Data reasearch was analized by Rank Spearman and Chi Square with level of significant based on p value